Comparative Analysis of the FIDIC Red Book Contract 2017 (Reprinted 2022) and the Indonesian National Construction Contract - Wahyu Moerhadi Nugroho; Sami’an Sami’an; Sarwono Hardjomuljadi (Interdisciplinary Social Studies, 2025)
The landscape of construction projects in Indonesia is becoming increasingly complex with the growing involvement of international funding and foreign contractors. The FIDIC Red Book 2017 has become the dominant global standard, while Indonesia operates under its own national construction law framework. This study aims to comparatively analyze the principles, mechanisms, and risk allocation in the FIDIC Red Book 2017 (Reprinted 2022) and the Indonesian national construction contract framework as reflected in the Construction Services Law and its derivative regulations. Using a normative literature study with a comparative law approach, the research identifies fundamental philosophical differences in risk management. FIDIC emphasizes fairness, balanced risk allocation, and structured procedural mechanisms (FIDIC, 2022; Soekotjo, 2019), whereas Indonesia’s national regulations tend to favor the Employer (government) with limited contractual flexibility (LKPP, 2021). The key findings lie in differences related to claim mechanisms, the role of the Engineer, and dispute resolution processes. This study contributes by providing a systematic comparative mapping useful for stakeholders—especially in hybrid international–national projects—and offers recommendations for harmonizing and improving contractual frameworks in Indonesian construction practice.